Sistem Informasi SMPN 24 Pesawaran Berbasis Web Mobile - Heru, Muhamad; Sundari, Las; Idris, Muhammad (JELTec (Journal of Learning Technology), 2024)
The rapid development of information technology encourages educational institutions to adopt digital systems to enhance the efficiency and effectiveness of data management and information services. This research aims to design and develop a mobile web-based information system for SMPN 24 Pesawaran as a solution to the limitations of the previously manual system. The system includes features for managing student and teacher data, class schedules, and academic information, all accessible in real-time via mobile devices. The development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance. The test results show that the system provides ease in data management and information delivery for all stakeholders, including teachers, students, and parents. With this mobile web-based information system, it is expected that administrative processes and communication within the school environment will become more effective and efficient.